Engineering Economy Application in Investment Evaluation: A Simulation Approach - Kholil, Muhammad; Haekal, Jakfat; Firdaus, Alfa; Almahdy, Indra; Riyadi, Selamet; Hidayat, Atep Afia (Journal of Information System, Technology and Engineering, 2025)
This study evaluates the feasibility of implementing an Enterprise Resource Planning (ERP) system in the Cosmetics and Household Needs sub-sector using engineering economics and system-dynamics simulation. The investment targets operational efficiency and the correction of transaction and inventory discrepancies. Financial viability was assessed via Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP), complemented by a multi-year Vensim simulation to capture dynamic cash-flow effects. Results indicate strong feasibility: NPV of Rp 119,654,313 over five years, IRR of 50.38% far above a 3.5% benchmark and a 7-month payback, with simulated trajectories showing increasing NPV and sustained positive cash flow under varying income, expense, and customer-growth assumptions. The ERP solution is at Technology Readiness Level (TRL) 7–8, reflecting prototype demonstration in an operational environment. The initiative aligns with institutional KPIs on digital transformation, efficiency, and financial performance, and supports SDG 9 (Industry, Innovation and Infrastructure) and SDG 12 (Responsible Consumption and Production) by promoting efficient resource management and sustainable industrial practices. Collectively, the evidence suggests ERP adoption is both financially sound and strategically beneficial for firms in this sub-sector.